Faktor Risiko Obesitas pada Mahasiswa di Universitas Ogan Komering Ilir Tahun 2025 - Jenny Sasmita Sari; Intan Kumalasari; Maliha Amin (Jurnal Rumpun Ilmu Kesehatan, 2025)
Obesity among college students is a public health issue that is gaining increasing attention because it is associated with an increased risk of chronic diseases such as diabetes mellitus, hypertension, and heart disease, and can reduce quality of life and academic productivity. College students, as a group of early adults, are in a transition phase towards independence and are therefore vulnerable to lifestyle changes, including unhealthy eating patterns, fast food consumption, low physical activity due to busy studies, irregular sleep habits, and high academic stress. This study aims to determine the risk factors associated with obesity among students at the Islamic University of Ogan Komering Ilir in 2025. This study used a cross-sectional design with a quantitative approach. A sample of 95 students was selected using a purposive sampling technique. Data were collected through a structured questionnaire and body mass index (BMI) measurement to determine respondents' nutritional status. Independent variables included diet, physical activity, sleep quality, stress levels, and a family history of obesity. The results showed a prevalence of obesity of 17.9%. Bivariate analysis found a significant association between obesity and unhealthy diet (p=0.002), low physical activity (p=0.000), poor sleep quality (p=0.000), and high stress levels (p=0.001). Meanwhile, a family history of obesity showed a tendency to have an effect but was not statistically significant. These findings indicate that obesity in college students is largely influenced by modifiable lifestyle factors. Therefore, this study emphasizes the importance of health promotion interventions on campus, such as balanced nutrition counseling, increased access to sports facilities, stress management, and education on healthy sleep patterns. Promotive and preventive efforts undertaken from a young age are expected to reduce the risk of obesity and chronic disease in the future.